2015
DOI: 10.1371/journal.pone.0140143
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Isolation of Three Different Stem Cell Populations from Murine Skin

Abstract: The skin is a rich source of readily accessible stem cells. The level of plasticity afforded by these cells is becoming increasingly important as the potential of stem cells in Cell Therapy and Regenerative Medicine continues to be explored. Several protocols described single type stem cell isolation from skin; however, none of them afforded simultaneous isolation of more than one population. Herein, we describe the simultaneous isolation and characterization of three stem cell populations from the dermis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Cells were obtained as described in ref. . Briefly, subcutaneous fat was removed from the skin with a scalpel, and the whole skin was placed dermis‐down in trypsin (Gibco) at 37 °C for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were obtained as described in ref. . Briefly, subcutaneous fat was removed from the skin with a scalpel, and the whole skin was placed dermis‐down in trypsin (Gibco) at 37 °C for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed in 4% w/v paraformaldehyde and subjected to immunofluorescence microscopy as previously described . The antibodies and their dilutions are listed in Supporting Information Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adherent cell colonies achieved from culture condition B displayed the most important markers and characteristics that a primary culture should possess to be classified as DMSCs [ 24 ]. Forni et al [ 25 ] reported simultaneously isolating and characterizing three stem cell populations from the dermis and epidermis of murine skin, namely epidermal stem cells, SKPs, and DMSCs. They believed DMSCs and SKPs could be isolated simultaneously from one skin sample and showed no overt difference with DMSCs and SKPs isolated in a routine way.…”
Section: Discussionmentioning
confidence: 99%
“…As there is a positive correlation between the IF stem cell proliferation and adherence, the proliferative IF stem cells can be distinguished from the low-adhered TA cells with the higher β1 integrins expression [20]. During terminal differentiation, the IF stem cells express involucrin, a differentiation marker, and filaggrin, an intermediate filament (IF)-associated protein [21,22].…”
Section: If Stem Cell Markersmentioning
confidence: 99%